Identifikasi Cacing Gastrointestinal pada Babi di Kabupaten Jayawijaya dan Paniai, Provinsi Papua: Identification of Gastrointestinal Worms in Pigs in the District of Jaya Wijaya and Paniai, Province of Papua - Isti Widayati; Bernadetta WI Rahayu; Noak Degei (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2020)
The rearing of pigs in the mountains of Papua is generally based on the free-range method during the daylight. Poor environmental sanitation and free-range management have been reported as risk factors of gastrointestinal worm infestation in pigs. In general, gastrointestinal parasite infestation can cause a loss of appetite, impede growth, decrease feed conversion rate, and increase vulnerabilities toward other pathogens. To add to that, the acute levels of infestation can cause death. Furthermore, some species can infest humans (zoonotic). As zoonotic parasites can impact the productivity and health of the people, it is crucial to identify the species of such parasites. This research was conducted in Umpakalo village at Kurulu district, Jayawijaya region, and three other villages namely Obaipugaida, Eyagitaida, and Ugituwataida at Ekadide district, Paniai region. Forty-five fecal samples from different pigs were used as the research material. The native method was used to identify the physical appearance of the eggs, and in turn, identify the species of the parasite. The data was analyzed in the tabulation form. The conclusion obtained in this research is that 95% of the fecal samples were infected by the gastrointestinal worms. Identified worms are Ascaris suum, Strongyloides ransomii, Trichuris suis, and Strongyle types. Most pigs have mixed infections.